Kajian Niat Berpindah Merek pada Perilaku Konsumen Produk Ramah Lingkungan - Adimas Rois Adnan (Pusat Riset dan Inovasi Nasional, 2026)
The increasing consumer awareness of environmental issues has encouraged companies to develop green product based marketing strategies to meet the growing demand for sustainability. This not only influences consumer preferences but also drives changes in consumer behavior, including brand switching intentions. This study aims to analyze the effect of green consumer experience on green consumer switching intention, with green consumer satisfaction acting as a mediating variable in this relationship. This research employs a quantitative approach using Structural Equation Modeling (SEM) with AMOS software. The subjects of this study consist of 168 respondents who are consumers of environmentally friendly detergents. The results indicate that green consumer experience has a positive and significant effect on green consumer satisfaction. Furthermore, green consumer satisfaction has a negative and significant effect on green consumer switching intention and serves as a mediating variable in the relationship between green consumer experience and switching intention. These findings imply that companies need to enhance the quality of environmentally based consumer experiences to create sustainable satisfaction and reduce the likelihood of brand switching.